Dielectric properties analysis of sulfur-containing models in coal and energy evaluation of their sulfur-containing bond dissociation in microwave field. (1st October 2016) - Tao, Xiuxiang; Tang, Longfei; Xie, Maohua; He, Huan; Xu, Ning; Feng, Li; Yang, Yancheng; Luo, Laiqin
Abstract: To evaluate the microwave response characteristic of different organic sulfur functional groups in coal, the dielectric properties of sulfur-containing and sulfur-free model compounds and mixtures of these compounds with pure coal were determined by a vector network analyzer (100 MHz–6.5 GHz). Results showed that for model compounds of similar structure, the dielectric properties of sulfur-containing model compounds were higher than those of the sulfur-free compounds. When frequency was increased, there was minimal change in the dielectric constant of model compounds, while the dielectric loss factor and dissipation factor varied greatly, with two peaks observed at 2–2.5 GHz and 4.5–5 GHz. These characteristic peaks were also present for the corresponding mixtures, indicating that the selective heating of organic sulfur functional groups in coal can be achieved at particular microwave irradiation frequencies. Additionally, carbon–sulfur bond dissociation times (C–S BDTs) of these model compounds were computed based on dielectric test results and carbon–sulfur bond dissociation enthalpies (C–S BDEs). The C–S BDTs of thioether and thiophene were found to significantly decrease after oxidation to sulfoxide and sulfone, respectively, suggesting that moderate oxidative pretreatment is conducive to breaking the C–S bonds in coal during microwaving.